Formulation and Characterization of Lemon Myrtle Essential Oil in Water Nanoemulsion Prepared Via Ultrasonication - Siti Noraini Bunawan; Noor Azlina Masdor; Nur Adeela Yasid, Mohd Izuan Effendi Halmi; Raviraj Mahabaleshwar Kulkarni; Mohd Yunus Abd Shukor, (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
This study focused on the formulation and characterization of a lemon myrtle essential oil-in-water nanoemulsion prepared via ultrasonication. The effects of key process parameters, specifically sonication power amplitude, sonication time, and surfactant concentration, were optimized based on droplet size, polydispersity index (PDI), and the stability of the nanoemulsion. Optimization of the formulation was achieved at 100% sonication power for 5 min, using 1% (w/w) lemon myrtle essential oil and 4% (w/w) surfactant, resulting in a droplet size of approximately 12.52 nm and a PDI of 0.153. Further characterization included physical appearance, droplet distribution, zeta potential, morphology, Fourier-transform infrared spectroscopy (FTIR), and storage stability. A clear nanoemulsion was obtained with a zeta potential of -38.1 mV, and transmission electron microscopy (TEM) revealed a spherical morphology. FTIR analysis confirmed that no chemical changes occurred in the components of lemon myrtle essential oil after ultrasonication. The nanoemulsion remained physically stable at both 25°C and 4°C for up to 180 days. In this work, a stable lemon myrtle essential oil-in-water nanoemulsion was successfully developed via ultrasonication-assisted processing. The developed nanoemulsion has promising applications in industries such as food, agriculture, and pharmaceuticals.